Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2017 - Seifried, Jürgen; Seeber, Susan; Ziegler, Birgit (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2017)
The Jahrbuch für Berufs- und Wirtschaftspädagogik (Yearbook on vocational and economic pedagogy) provides an overview over the current state of relevant research. This section takes into account the broad thematic and methodological spectrum of research and theory formation in vocational and business education.